Measuring the quality of government services provided to customers at the Citizen Service Center in Lattakia Governorate (Journal of Hama University, 2022)
This study aimed to measure the quality of services provided at the Citizen Service Center in Lattakia Governorate from the point of view of the center's clients. Using the Servqual scale, the service gap measures between perceived quality and expected quality. The researcher relied on the descriptive method of analysis. To achieve the objectives of the study, the researcher collected primary data using a questionnaire designed by looking at previous studies for the five basic dimensions of service quality (reliability, tangibility, response, assurance, sympathy), and the study population is made up of the center’s clients; Where random sampling was used to select the study sample, which consisted of (325) individuals. The results of the study showed; There is a gap in the level of quality of services provided to customers at the Citizen Service Center in Lattakia Governorate; As the level of quality of the expected services is higher than the level of the quality of the perceived services, with significant differences of statistical significance between the level of quality of the perceived and expected services provided to the clients of the Citizen Service Center in Lattakia Governorate, and then the researcher presented a set of recommendations to improve the quality of services provided at the Citizen Service Center in Latakia Governorate.
Keywords: services - quality of services - citizen service center